ANALISIS PENGARUH HARGA CPO (CRUDE PALM OIL) DUNIA DAN PRODUKSI CPO (CRUDE PALM OIL) INDONESIA TERHADAP FLUKTUASI HARGA MINYAK GORENG CURAH INDONESIA - Tri Yulianto; Rhevi HS Putri; Nur Khotimah (Jurnal Cakrawala Ilmiah, 2022)
Commodity of cooking oil is one of the nine basic ingredients that are strategic and have an important role in the Indonesian economy. Almost all levels of society use cooking oil for their daily needs or production needs. In the fourth quarter of 2021 until now, the price of domestic cooking oil rose significantly. The purpose of this study was to determine the effect of fluctuations in world CPO oil prices and Indonesian CPO production on fluctuations in Indonesian bulk cooking oil prices. The writing method used is quantitative with multiple linear regression approach. The results showed that fluctuations in world CPO prices had an effect on fluctuations in Indonesian bulk cooking oil prices and Indonesian CPO production had no effect on fluctuations in Indonesian bulk cooking oil prices. So in this paper the author recommends the government to take anticipatory and preventive measures against the turmoil caused by fluctuations in the price of Indonesian bulk cooking oil, such as eradicating cooking oil cartels and programs to maintain people's purchasing power